Assessing the Impact of Organizational and Personal Factors on Employee Absenteeism - A.M.N.M. Gangananda; W.M.A.H. Bandara; R.A.D.D.N. Ranatunga; P.G.S.S. Pattiyagedara (International Journal of Engineering and Management Research, 2022)
A hotel's economic feasibility and progress depend on the efficient use of all resources, along with human resources (HR). Absenteeism is a critical issue that almost all employers encounter daily. It imposes considerable financial burdens on organizations and has a negative impact on productivity and performance. The majority of research has revealed that absenteeism is a multifaceted construct impacted by numerous factors, both personal and organizational. Although researchers have attempted to identify the factors that contribute or are associated to absenteeism in order to devise suitable solutions. The research on the relationship between organizational and personal factors and absenteeism appears to be contradictory. A few studies found no correlation between these two variables, whereas some found a weak to moderate correlation between the two variables. Furthermore, there are few research studies on absenteeism in the Sri Lankan hotel industry. As a result, the current study sought to ascertain whether organizational and personal factors influence absenteeism in selected 3-5 star grade tourist hotels in the Galle District. The 14 three to five-star tourist hotels in Galle District were the study's target population. The sample size was determined using a non-probable random sampling method. As a result, a sample of five three to five star tourist hotels in the Galle District was preferred. A questionnaire was used to collect primary data from respondents for the study. The Statistical Package for Social Sciences (SPSS) was used for analysis, which allowed the researcher to express the data in the form of tables and figures. Previous research has discovered that there are several factors that can influence employee absenteeism. According to the literature review, factors such as promotion satisfaction, coworker support, pay satisfaction, age, gender, tenure, number of dependents, and marital status can all have an impact on absenteeism.